Watering Station Best Management Practices for Container Nurseries - Tom Yeager (EDIS)
Watering stations are specialized irrigation structures where plants are watered immediately after transplanting. Water not retained by the container substrate as well as water falling between containers becomes runoff. This runoff can contain sediment and nutrients, such as nitrogen and phosphorus, that can impact natural waters if not managed according to Best Management Practices (BMPs). The purpose of this new 3-page fact sheet is to provide examples of how runoff from watering stations at two nurseries was managed after implementation of the BMP. Written by Tom Yeager and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep590